The price of justice: cost neglect increases criminal punishment recommendations - Aharoni, Eyal (Legal and criminological psychology, 2020)
PURPOSE-At what cost to society are we willing to punish criminal offenders, and how does our awareness of those costs impact our support for punitive measures? In a nationally distributed sample of 191 Internet users, we examined the elasticity of punishment in response to information about the direct material cost of incarceration.METHODS-Using an experimental vignette method with a within-subjects design, we manipulated the salience of the direct costs (low, high, or externalized) and the expected cost size (from low to high across eight intervals).RESULTS-As predicted, (1) when costs were made salient, cost increases reduced punishments, consistent with rational economic principles, (2) but when costs were not salient, punishments reached levels indistinguishable from those made under personally cost-free conditions. (3) Cluster analysis revealed the operation of at least three distinct punishment types: punishments that were relatively harsh even at high cost, as predicted by a conservative, deontological stance; those that were relatively lenient and similarly inelastic, as predicted by a politically liberal deontological stance, and those that decreased with cost increases, as predicted by a politically moderate, consequentialist stance.CONCLUSIONS-Our results suggest that judgements about the utility of punishment are shaped by competing ideological and rational strategies, and how people trade off between these strategies depends in part on cost salience. We discuss the implications of these findings for discourse on transparency in sentencing.